Penerapan Model Problem Based Learning Berbantuan ICT Pada Mata Pelajaran PPKn Kelas 8 - Jemius Dufantri Ghega; Didik Iswahyudi; Romadhon Romadhon (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Quality education requires a quality learning process. Quality learning is certainly designed in learning activities that use learning methods that are in accordance with the eyes taught by the teacher so as to assist the teacher in giving directions so that students can understand the content delivered by the teacher. In reality, education in Indonesia has decreased the quality of learning in the context of an independent curriculum. There are research findings called learning loss and learning gap devices in this problem. So it is expected that subject teachers must be able to restore the declining level of learning quality. So researchers use a problem-based learning model. Where this problem-based learning model can solve problems and increase students' knowledge. The purpose of the study was to analyze the implementation of problem-based learning in improving the quality of PPKn learning at SMP Negeri 19 Malang. The method used in this research is qualitative case study method. Data collection techniques based on observation, interviews and document research. The result of this study is the application of the ICT-assisted problem-based learning model showing that a significant change because students are directed to examine problems in learning activities using problem-based teaching methods that have a positive impact on student achievement outcomes. Based on the results of the research, researchers can conclude that the application of ICT-assisted problem-based learning models in class VIII PPKn subjects of SMP Negeri 19 Malang students can solve problems in groups given by teachers.